Discovery of Diffuse γ-Ray Emission in the Vicinity of G213.0-0.6: Supernova Remnant versus the Massive Star-forming Region - Yuan Li; Gwenael Giacinti; Siming Liu (The Astrophysical Journal)
We report the discovery of high-energy γ -ray emission in the vicinity of G213.0-0.6, which is debated as a supernova remnant (SNR) or an ionized hydrogen (H _II ) region. Using 16 yr Pass 8 data from Fermi Large Area Telescope, we found three extended sources with different photon spectra in this region, which we label as SrcA, SrcB, and SrcC. Among them, the γ -ray source SrcA with a log-parabola spectrum is spatially coincident with a star-forming region and several OB stars. The power-law spectra source SrcB is spatially coincident with an SNR radio shell. SrcC, with a harder power-law photon spectrum, is located outside of the radio shell structure. All of them are spatially coincident with a dense molecular cloud (MC) in the velocity range of 35–54 km s ^−1 . In this scenario, SrcB can be interpreted as the GeV counterpart of the SNR, and its γ -ray emission originates from the shock–cloud interaction. SrcA and SrcC originate from the escaped CRs illuminating a nearby MC. For SrcA, another possibility is that the γ -ray emission originates from a young stellar cluster associated with a star-forming region; however, the supporting evidence remains insufficient to draw a definitive conclusion.